Pure Organic Active Compounds Against Abiotic Stress: A Biostimulant Overview - García-García, Ana L.; García-Machado, Francisco J.; Borges, Andrés A.; Morales-Sierra, Sarai; Boto, Alicia; Jiménez-Arias, David (Frontiers in Plant Science, 2020)
Biostimulants are probably one of the most promising alternatives nowadays to face yield losses caused by plant stress, which are intensified by climate change. These are a large group that includes a range of compounds with positive effects on plants, excluding pesticides and chemical fertilizers. The normal application route has consisted of mixtures such as lixiviates from proteins or algal extracts, but nowadays companies are interested in more specific compounds that are capable of increasing tolerance against abiotic stress. Individual application of a single compound offers researchers the opportunity to learn more about the plant defence process itself and to aid the agrochemical industry in developing these new products. This review attempts to summarise the state of the art regarding various families of compounds that are able to enhance growth. It focuses on their action mechanism and how they can help maximize agricultural yields under stress conditions exacerbated by climate change.